Different denitrification potential of aquic brown soil in Northeast China under inorganic and organic fertilization accompanied by distinct changes of nirS- and nirK-denitrifying bacterial community - Yin, Chang; Fan, Fenliang; Song, Alin; Li, Zhaojun; Yu, Wantai; Liang, Yongchao (European journal of soil biology, 2014)
The impacts of long-term application of inorganic and organic fertilizers on the activity, community composition, and abundance of denitrifying bacteria in an aquic soil of Northeast China were analyzed in this study. Denitrifying taxa were characterized for their nitrite reductase genes, nirS and nirK. The results showed that addition of inorganic fertilizer to soil decreased potential denitrification enzyme activity (DEA) by 41.1%, and this effect was mirrored by a reduction (39.0%) in the nirS-, but not nirK-denitrifiers' abundance. Addition of organic fertilizer increased DEA by 41.3% but had no impact on the abundance of either nirS- or nirK-denitrifiers. Inorganic fertilization strongly altered the community structure of nirK but only marginally impacted the community structure of nirS-denitrifiers; organic fertilizer had no influence on the community structures of these two guilds. DEA was significantly correlated with community structure of nirK-denitrifiers, but not with community structure of nirS-denitrifiers and abundances of both nirK- and nirS-denitrifiers. Moreover, community structure of nirK-denitrifiers was significantly correlated with pH, while nirS-denitrifiers were impacted by soil pH, total phosphorus (TP), and Olsen phosphorus (Olsen P) status. Our results suggest that different influences of inorganic and organic fertilization on DP are linked to a distinct structural change of nirS- and nirK-denitrifying bacterial communities in this aquic brown soil. •A comprehensive exploration of denitrifiers population in an aquic brown soil was provided.•Inorganic fertilization exerted stronger influences on denitrifiers population than organic fertilization.•A differential response pattern to fertilization was observed between nirK- and nirS-denitrifiers populations.•pH was the dominant factor controlling the shift of denitrifiers population in this soil type.